Arteriovenous malformation presenting as a lip swelling - Ashok Kumar Ariboyina; Ozgur Tatli; Lakshmi Goriparthi; Narendra Achanta; Suresh Kumar Thirumoothy; Suha Turkmen (Clinical Case Reports, 2023)
Key Clinical Message Arteriovenous malformations (AVM) are extremely rare on the face and especially on the lip. Lip can be more easily exposed to traumas due to their anatomical location. Especially superficial AV malformations are very susceptible to trauma and can bleed very seriously after being exposed to such effects. AVMs management generally based on their hemodynamic characteristics and growth modalities. The surgical treatment requires elaborate planning and multidisciplinary approach. When evaluating a mass with a clinical manifestation of lip swelling, ruling out a vascular anomaly before any intervention is also crucial. Abstract Arteriovenous malformations (AVM) are abnormal fistulas between an artery and a vein, without an intervening capillary bed. AVM may occur everywhere in the body, with the brain being of particular concern, as AVM can be complicated by bleeding. Herein, we present the case of a patient with a very atypical AVM location consisting of a lip mass. Given the possibility of hemorrhage and airway obstruction, early detection and timely intervention are mandatory.